ICHTHYOPLANKTON OF BRANSFIELD STRAIT - ANTARCTICA - Sinque, Chossi; Koblitz, Sigrid; Costa, Laura Marília (Revista Nerítica, 1986)
A preliminary study on the distribution and abundance of ichthyoplankton related with ecological data were made during the southern summer 1982/83 from material collected from the oceanographic R/V “ Professor W. Besnard” in the Bransfield Strait — Antarctica. From 210 larvae caught in the area, 10 species were identified: Pleuragramma antarcticum, Notothenia larseni, Notothenia gibberifons, Notothenia kempi, Notothenia nudifrons (Nototheniidae); Notolepis coatsi (Paralepididae); Electrona antarctica (Myctophidae); Artedidraco skottsbergi, Harpagifer bispinis (Harpagiferidae) and Champsocephalus gunnari (Channichthyidae). Besides this, the spawning period and occurrence of larvae related with water masses were considered. ICTIOPLÂNCTON DO ESTREITO DE BRANSFIELD — ANTÁRTICA Estudo preliminar sobre distribuição e abundância de ictioplâncton relacionado com os dados ecológicos foi realizado durante o verão austral 1982/83 com o material coletado a bordo do N/Oc. “ Professor W. Besnard” , no Estreito de Bransfield — Antártica. Dos 210 exemplares de larvas capturadas na área, 10 espécies foram identificadas: Pleuragramma antarcticum, Notothenia larseni, Notothenia gibberifrons, Notothenia kempi, Notothenia nudifrons (Nototheniidae); Notolepis coatsi (Paralepididae); Electrona antarctica (Myctophidae); Artedidraco skottsbergi, Harpagifer bispinis (Harpagiferidae) and Chanrtpsocephalus gunnari (Channichthyidae). Paralelamente foram considerados o período de desova e a ocorrência das larvas relacionada com massas de água.